Impact of brain-based instructional strategy on students' attitude to senior secondary school mathematics in Oyo State, Nigeria (2011)
This study investigated the impact of brain-based instructional strategy on students' attitude to Senior Secondary School Mathematics. A pre-test, post-test, control group quasi- experimental design was adopted with a 2 ×3 ×2 factorial matrix. The sample was 522 Senior Secondary School II Students from nine randomly selected schools in Oyo State, Nigeria. Five schools were randomly assigned to the experimental group (Brain-based Instructional Strategy- BBIS), while four schools were assigned to the control group (Non-Brain-based Instructional Strategy - NBBIS). The instruments were: Mathematics Attitude Questionnaire (r=0.83), Cognitive Style Test (r=0.81) and Mathematics Anxiety Rating Scale (r-0.81). One research question and one hypothesis guided the study. Data obtained from the research questions were analysed using mean scores while the hypothesis was tested at 0.05 level of significance, using the analysis covariance (ANCOVA). Brain-based instructional strategy was more effective at improving students' attitude to mathematics than the conventional method. Teachers of Mathematics could therefore adopt brain-based instructional strategy for teaching secondary school students.